Environmental Criminology : Spatial Analysis and Regional Issues. - Leonard, Liam (Emerald Publishing Limited, 2017)
Using sociological, criminological, anthropological, historical and media analysis, this multi-disciplinary volume examines local and regional issues in environmental criminology.
""Spatial Models: The Growth and Spread of Ice""
Keywords: Crime -- Environmental aspects.; Criminology.; Human beings -- Effect of environment on.; elektronické knihy; electronic books